Integrin-activating Yersinia protein Invasin sustains long-term expansion of primary epithelial cells as 2D organoid sheets - Joost J.A.P.M. Wijnakker; Gijs J.F. van Son; Daniel Krueger; Willine J. van de Wetering; Carmen Lopez-Iglesias; Robin Schreurs; Fenna van Rijt; Sangho Lim; Lin Lin; Peter J. Peters; Ralph R. Isberg; Claudia Y. Janda; et al. (Proceedings of the National Academy of Sciences, 2025)
Matrigel ® /BME ® , a basement membrane-like preparation, supports long-term growth of epithelial 3D organoids from adult stem cells [T. Sato et al. , Nature 459 , 262–265 (2009); T. Sato et al. , Gastroenterology 141 , 1762–1772 (2011)]. Here, we show that interaction between Matrigel’s major component laminin-111 with epithelial α6β1-integrin is crucial for this process. The outer membrane protein Invasin of Yersinia is known to activate multiple integrin–β1 complexes, including integrin α6β1. A C-terminal integrin-binding fragment of Invasin, coated on culture plates, mediated gut epithelial cell adhesion. Addition of organoid growth factors allowed multipassage expansion in 2D. Polarization, junction formation, and generation of enterocytes, goblet cells, Paneth cells, and enteroendocrine cells were stable over time. Sustained expansion of other human, mouse, and even snake epithelia was accomplished under comparable conditions. The 2D “organoid sheet” format holds advantages over the 3D “in gel” format in terms of imaging, accessibility of basal and apical domains, and automation for high-throughput screening. Invasin represents a fully defined, affordable, versatile, and animal-free complement to Matrigel ® /BME ® .